RESTORATION AT THE BOUNDARY: A SOCIO-ECOLOGICAL PERSPECTIVE ON MANAGEMENT IN THE GREATER EVERGLADES ECOSYSTEM - Sabin, John Edward, III (East Carolina University)
How will conservation areas in South Florida continue to change because of ongoing restoration efforts? Ecosystem restoration practitioners in the Global North aim for adaptive management during a time of increasing uncertainty. To reconcile competing socio-ecological futures in South Florida, this project integrates discursive narrative analysis, spatial modeling, and intuitive data visualization to guide a holistic monitoring approach during the restoration of the Florida Everglades. Projects like the East Coast Buffer (ECB) and the Western Everglades Restoration Project (WERP) represent ongoing attempts in Everglades restoration to acquire and protect degraded landscapes adjacent to protected areas, such as Everglades National Park and the Big Cypress Preserve. This interdisciplinary framework seeks to build a socio-ecological model to monitor ecosystem restoration and holistically track affected cultural landscapes at the periphery of the built environment. Insights provided through this research suggest that panarchy as a conceptual tool best facilitates the co-production of knowledge in large-scale restoration projects threatened by environmental amnesia. I developed a landcover change ranking system through expert knowledge consultation, remote sensing, and GIS to understand the shifting physiognomic structure of landscapes affected by restoration activities in the ECB. I bridge this modeling framework into the content of WERP to showcase how the restoration game progresses under new challenges to the role of wilderness in South Florida. The insights provided through this investigation also guide the ongoing development an ArcGIS Story Map that accompanies this research. This online spatial presentation platform integrates the research components of the greater project into a place-based narrative intended to assist with collaboration, education, and planning.
Keywords: GIS; Story Map; Restoration ecology--Florida--Everglades; Conservation biology--Florida--Everglades; Political ecology--Florida--Everglades; Remote sensing--Florida--Everglades